2009
DOI: 10.1002/cncy.20004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the diagnosis of low‐grade squamous intraepithelial lesion, cannot exclude high‐grade squamous intraepithelial lesion

Abstract: The similarity of histologic follow-up results between LSIL-H and ASC-H suggested that the management of women who have a diagnosis of LSIL-H should be similar to the management of women who have a diagnosis of ASC-H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
34
1
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 28 publications
12
34
1
6
Order By: Relevance
“…We obtained similar values between aSC-H, and LSiL and HSiL as regards determining Cin2 or higher lesions of LSiL-aSC-H. Past studies have reported similar results (2,8,16 in conclusion, we believe that LSiL/aSC-H should be classified as a separate category as there is a high chance of defining the underlying Cin2 and that it should therefore be evaluated separately from LSiL. We found that LSiL/ aSC-H had a high risk of a Cin2 or higher neoplasia like aSC-H but that it had low risk for Cin3 in contrast.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…We obtained similar values between aSC-H, and LSiL and HSiL as regards determining Cin2 or higher lesions of LSiL-aSC-H. Past studies have reported similar results (2,8,16 in conclusion, we believe that LSiL/aSC-H should be classified as a separate category as there is a high chance of defining the underlying Cin2 and that it should therefore be evaluated separately from LSiL. We found that LSiL/ aSC-H had a high risk of a Cin2 or higher neoplasia like aSC-H but that it had low risk for Cin3 in contrast.…”
Section: Resultssupporting
confidence: 83%
“…This rate was higher than with LSiL (0%), aSC-H (8%) and HSiL (13%). Hang et al (18) and alsharif et al (8). have also reported that biopsies of patients diagnosed with LSiL/aSC-H have a higher rate of Cin2 diagnosis when found to have a Cin2 or higher lesion and LSiL/aSC-H probably indicates Cin2 as also reported by these authors.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…18 This is consistent with the results obtained from the majority of the studies observed, which demonstrated CIN II+ prevalences of more than 40%, according to the biopsy results. 3,5,6,[17][18][19][20][21][22][23][24]29 Our results confirmed that at the time of the first ASC-H report, immediate intervention with colposcopy was necessary, followed by a biopsy. This validates the medical management of ASC-H that is required by the "management algorithm from the time of the first atypical Pap, " which is included in the Chilean Ministry of Health's Clinical Guidelines for Cervical Cancer.…”
Section: Asc-h Issupporting
confidence: 71%